Ventricular and vascular stiffening in ischemia with no obstructed coronary arteries: novel insight from pressure-volume analysis. (3rd October 2022) - Oneglia, A P; Wei, J; Samuels, B; Jake Samuel, T; Azarbal, B; David Anderson, R; Petersen, J W; Cook-Weins, G; Pepine, C J; Noel Bairey Merz, C; Nelson, M D
Abstract: Background: Ischemia with no obstructed coronary arteries (INOCA) is prevalent among women and associated with an increased risk of developing heart failure with preserved ejection fraction (HFpEF), however the mechanism linking these conditions remains poorly understood. Coronary vascular dysfunction is common in INOCA, representing a putative mechanism driving heart failure progression. Purpose: To evaluate the role of coronary vascular dysfunction on left ventricular (LV) function in women with INOCA. Methods: Women with suspected INOCA, defined as having signs and symptoms of ischemia but no obstructive coronary artery disease, underwent LV pressure-volume assessment at rest and during 3 minutes of isometric handgrip stress at 30% of maximal voluntary contraction. Coronary function testing was performed by infusing standard doses of adenosine, acetylcholine, and nitroglycerine through a guiding catheter placed in the left main coronary artery, per our published protocols. Using standardized definitions of normal versus abnormal responses, cases with zero abnormal coronary pathways (n=12) were compared to cases with three abnormal coronary pathways (n=7). Results: At rest, end-systolic pressure and end-systolic elastance were elevated in cases with abnormal coronary vascular function (Figure), while normalized peak filling rate was lower (0.45±0.15 s mmHg –1 vs 0.37±0.08 s mmHg –1 ). With isometric handgrip, end-systolic pressure and end-systolic elastance increased similarly between groups, remaining highest in those with abnormal coronary vascular function (Figure). End-diastolic pressure-volume declined with handgrip in those without coronary vascular dysfunction, while increasing (up and to the left) in those with coronary vascular dysfunction (Figure). Likewise, normalized peak filling rate improved with handgrip in those without coronary vascular dysfunction, but did not change in those with coronary vascular dysfunction (0.66±0.37 s mmHg –1 vs 0.38±0.15 s mmHg –1 ). Conclusions: We show heightened ventricular and vascular stiffness in women with INOCA who have abnormal coronary vascular function. These preliminary data support the hypothesis that coronary vascular dysfunction may be a putative mechanistic pathway driving heart failure progression in INOCA. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): National Institutes of Health